Cabinet composition and assessment of a multiparty presidential system - Mauerberg Junior, Arnaldo (2016)
This doctoral dissertation provides a detailed analysis of the Brazilian cabinet according to the concepts of a multiparty presidential system. Appointing politicians as ministers is one of the most important coalition-building tools and has been widely used by minority presidents. This dissertation will therefore analyze the high-level Brazilian national bureaucracy between 1995 and 2014. It argues that the ministries – or departments – are not equal, and that allied parties therefore take into account the different characteristics of a ministry when demanding positions as a patronage strategy or for use as other kinds of political assets. After reviewing the literature on the theme, followed by a comparative analysis of the Brazilian, Chilean, Mexican, and Guatemalan cabinets, all the Brazilian ministries will be weighed and ranked on a scale that is able to measure their political importance and attractiveness. This rank takes into account variables such as the budgetary power, the ability to spend money according the ministers’ will, the ability to hire new employees, the ministries’ influence over other governmental agents such as companies, agencies, and so on, the ministers’ tenure in office. Finally, a proxy is provided that seeks to identify the normative power a department may hold. All of these characteristics will then be taken into account in considering the representatives’ opinion, thus helping to ascertain whether the cabinet appointment has been coalescent among the several parties that belong to the president’s coalition.